História de vida de uma professora surda e sua prática pedagógica na educação básica - Mazzacotte, Andrea Carolina Bernal (2018)
This paper is an auto-biography of the deaf professor Andréa Carolina Mazacotte, born in São Paulo, 1979. Graduated in Normal Superior in a private university in Foz do Iguaçu and in Arts of Teaching/Libras (Brazilian Sign Language) in the Universidade Federal de Santa Catarina. Worked as Brazilian Sign Language (Libras) professor for higher education and also has already taught as a teacher for deaf people from preschool education up to Teens and Adults Education. The problem to be discussed on this paper is:” How do the deaf’s fight/struggle for education? And, after all, what is bilingual education for the deaf?”. From the professor’s auto-biography method is possible to see the relationship between the deaf professor’s life story, this papers author, and the deaf historical struggle for their rights in education and in having their own language, as they were advertised and reported in newspapers and magazines. For this to take place, it presents documental research in newspapers and magazines that shows the personal history and the history of the deaf’s fight/struggle for education. This paper also has as its general objective to register the fight/struggle of the deaf for education, understanding what is bilingual education for the deaf and conceptualize the bilingual education for the deaf, pointing out teaching methodology ideas for Libras (Brazilian Sign Language) as a first language (L1) and Portuguese in the written category as a second language (L2). And the specific objectives would be on how to present the formative process of a deaf professor. The auto-biographical approach, based on Nóvoa (1992), is explained for the fact that the teacher/professor experience may help understanding the development of the deaf teachers and professors. The second chapter approaches the history of the deaf education in Brazil and worldwide. The third shows the auto-biography, discussing the deaf culture and education and the struggle from the deaf community for their right to have their own language. The fourth chapter exhibits the pedagogical practice in the bilingual education for and to the deaf, associating with the educational theory from Paulo Freire. As we could conclude, the bilingual education for the deaf needs to be rethought in order that the deaf learn Libras (Brazilian Sign Language) significantly, which unfortunately is not happening in the today’s scenario in which the main language is Portuguese and Libras is taught only as a signalization, in other words, not respecting the grammatical points from Libras, only imitating the Portuguese structures. The deaf, to be part of the society, need schools that respect Libras and the deaf culture, for that is the only way that it will be possible to raise active and critical citizens that do not depend on assistentialism and paternalism. The words for the deaf need to have meaning.